A simple and reproducible capacitive electrode. Issue 3 (March 2016) - Spinelli, Enrique; Guerrero, Federico; García, Pablo; Haberman, Marcelo
Highlights: Bootstrapping techniques, with current low offset voltage CMOS operational amplifiers, allow implement capacitive electrodes with standard components and Printed Circuit Board materials, and fulfilling ECG transient response requirements. The complete circuit of the capacitive electrode is presented. The proposed circuit, with a minimal number of parts, also provides a fast recovery feature. Abstract: Capacitive Electrodes (CE) allow the acquisition of biopotentials through a dielectric layer, without the use of electrolytes, just by placing them on skin or clothing, but demands front-ends with ultra-high input impedances. This must be achieved while providing a path for bias currents, calling for ultra-high value resistors and special components and construction techniques. A simple CE that uses bootstrap techniques to avoid ultra-high value components and special materials is proposed. When electrodes are placed on the skin; that is, with coupling capacitances C S of around 100 pF, they present a noise level of 3.3 µVRMS in a 0.5–100 Hz bandwidth, which is appropriate for electrocardiography (ECG) measurements. Construction details of the CE and the complete circuit, including a fast recovery feature, are presented.